Application of SFCA pedestrian simulation model to the signalized crosswalk width design. (October 2015) - Lili Lu, A.; Gang Ren, B.; Wei Wang, C.; Ching-Yao Chan, D.
Highlights: This study presents a new approach for specifying the design of the signalized crosswalk width. A crossing time estimation model is proposed and developed by taking the time lag of pedestrian platoons as well as bi-direction effects into consideration. Two important indicators are introduced into the evaluation of pedestrian crossing efficiency and comfort level respectively. The relationships among indicators as well as the crosswalk width and pedestrian demand are modeled and illustrated. Abstract: This study presents a new approach for specifying the design of the signalized crosswalk width. Based on the analysis of the characteristics of bi-direction pedestrian flows at the subject signalized crosswalk, a crossing time ( CT ) estimation model is proposed and developed by taking the time lag of pedestrian platoons as well as bi-direction effects into consideration. Subsequently, two important indicators (proportion of delay in the crossing time, i.e. PDC, and local density level, i.e. LDL ) are introduced into the evaluation of pedestrian crossing efficiency and comfort level respectively. It is shown in our work that CT, PDC, and LDL can be successfully obtained with the implementation of cellular automaton into the pedestrian simulation model by incorporating social forces (SFCA). Moreover, the relationships among CT, PDC, and LDL as well as the crosswalk width and pedestrian demand are modeled and illustrated. By synthesizing all indicators, a method is introduced to determine the recommended maximum and minimum widths for signalized crosswalks under different pedestrian demand volumes. Our methodologies demonstrate that they may help traffic engineers and specialists make a sensible choice of the crosswalk width. The outcome of our work will further give traffic engineers and practitioners new insights for the design and planning of signalized pedestrian crosswalks and constitute an important contribution to the understanding and evaluation of pedestrian movements in this aspect.